2002
DOI: 10.1038/sj.ejcn.1601474
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction, glomerular filtration rate and albuminuria in patients with type 2 diabetes mellitus: a randomized trial

Abstract: Objective: Protein restriction delays the progression of non-diabetic and type 1 diabetic renal disorders. This study assessed whether protein restriction delays the onset or early progression of renal disorders in type 2 diabetes. Design: Randomized controlled trial. Outcomes were albuminuria (mg=24 h) and, as an estimate of the glomerular filtration rate, cimetidine-influenced creatinine clearance. Setting: Primary care. Subjects: Patients with type 2 diabetes and microalbuminuria or at least detectable albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 35 publications
(57 reference statements)
0
41
0
1
Order By: Relevance
“…In the present study there were no changes in urinary albumin excretion in either group. Cross-sectional [41] and clinical studies [42] in people with diabetes have not shown an association between protein intake and albumin excretion nor a beneficial effect of chronic protein restriction on the course of albuminuria or on prevention/delaying of renal damage. Similarly, Skov and co-workers [43] found no changes in urinary albumin excretion between obese, healthy subjects consuming as much as they wanted of either a low-fat, high-protein or low-protein diet (25% vs 12% of energy as protein) over 6 months, and that changes in urinary albumin excretion were inversely correlated with dietary protein intake.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study there were no changes in urinary albumin excretion in either group. Cross-sectional [41] and clinical studies [42] in people with diabetes have not shown an association between protein intake and albumin excretion nor a beneficial effect of chronic protein restriction on the course of albuminuria or on prevention/delaying of renal damage. Similarly, Skov and co-workers [43] found no changes in urinary albumin excretion between obese, healthy subjects consuming as much as they wanted of either a low-fat, high-protein or low-protein diet (25% vs 12% of energy as protein) over 6 months, and that changes in urinary albumin excretion were inversely correlated with dietary protein intake.…”
Section: Discussionmentioning
confidence: 96%
“…An increasing body of evidence suggests that dietary pattern intake rather than a sole focus on individual nutrients may offer a more practical approach to dietary management of chronic diseases (122-124). (126)(127)(128)(129)(130)(131)(132)(133).Theeffectsofalow-protein (daily intake of 0.6 g protein/kg ideal body weight), low-phosphorus (500-1,000 mg/day) diet were compared with those of a control diet containing $1.0 g protein/kg ideal body weight per day and $1,000 mg phosphorus per day in 35 patients with type 1 diabetes and DKD. Study participants on the lowprotein, low-phosphorus diet had a slower rate of decline in iothalamate GFR over the course of the study.…”
Section: Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…Tables 1 and 2 display the detail of each of the studies (by size of the study) that did report a dietary assessment method. In total 50 studies (20.6%) did not report the dietary assessment method used (Janatuinen et al, 1995;Sacks et al, 1995;Conlin et al, 2000;Fan et al, 2000;Kauwell et al, 2000;Knopp et al, 2000;Vuksan et al, 2000;Gregory et al, 2001;Lietz et al, 2001;Moore et al, 2001;Svetkey et al, 2001;Vollmer et al, 2001;Janatuinen et al, 2002;Pijls et al, 2002;Shankar et al, 2002;Vicennati et al, 2002;Allison et al, 2003, Berg et al, 2003Engstrom et al, 2003;Facchini et al, 2003;Gluck and Gebbers, 2003;Hadley et al, 2003;Hoyt et al, 2003;Khan et al, 2003;Upritchard et al, 2003;Vozzo et al, 2003;Wolfe et al, 2003;Xiao et al, 2003; Writing group of the PREMIER Collaborative Research Group, 2003;Chen et al, 2004;Maubach et al, 2004;McGuire et al, 2004;Miyashita et al, 2004;Parra et al, 2004;Sagara et al, 2004;Westerterp-Plantenga et al, 2004;Davey Smith et al, 2005;Svetkey et al, 200...…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the FFQ method may also be administered by the above means but can also vary significantly in the number of food items or food groups included with nested food groups appearing to be better suited to this method (Thompson et al, 2002). The number of food groups overall and the portion size associated with them is also likely to influence not only the duration of the assessment itself and in turn the quality of the responses given with (Sacks et al, 1995, Conlin et al, 2000, Knopp et al, 2000, Pijls et al, 2002, Allison et al, 2003, Berg et al, 2003, Facchini et al, 2003, Gluck and Gebbers, 2003, Hadley et al, 2003, Hoyt et al, 2003, Upritchard et al, 2003, Writing group of the PREMIER Collaborative Research Group, 2003, Chen et al, 2004, McGuire et al, 2004, Westerterp-Plantenga et al, 2004, Lejeune et al, 2005, Davey Smith et al, 2005, Benito et al, 2006, Han-Geurts et al, 2007, Cheskin et al, 2008, Due et al, 2008, Sathiaraj et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation